Environmental Ethics - Mfonobong David Udoudom; Okpe Okpe; Timothy Adie; Samuel Akpan Bassey (Budapest International Research and Critics University, 2019)
Environmental ethics is an area that investigates the question of which ethical norms are appropriate for governing human interactions with the natural environment. Considered a branch of applied or practical ethics, environmental ethics has only existed as a subject since the late 1970s. However, concern about environmental problems is growing, and many philosophers claimed that the mainstream of ethics' only focus on humans' relationships with other humans leaving behind clear theoretical framework for ethically evaluating the relationship among humans and the nonhuman natural world. In response to this position, they recommended that a new field of inquiry was needed to investigate this matter directly. This paper looks into the thrust of environmental ethics.